Atomically-detailed folding simulation of the B domain of staphylococcal protein A from random structures - Vila, Jorge Alberto (2003)
The conformational space of the 10–55 fragment of the B-domain of staphylococcal protein A has been investigated by using the electrostatically driven Monte Carlo (EDMC) method. The ECEPP/3 (empirical conformational energy program for peptides) force-field plus two different continuum solvation models, namely SRFOPT (Solvent Radii Fixed with atomic solvation parameters OPTimized) and OONS (Ooi, Oobatake, Némethy, and Scheraga solvation model), were used to describe the conformational energy of the chain. After an exhaustive search, starting from two different random conformations, three of four runs led to native-like conformations. Boltzmann-averaged root-mean-square deviations (RMSD) for all of the backbone heavy atoms with respect to the native structure of 3.35 Å and 4.54 Å were obtained with SRFOPT and OONS, respectively. These results show that the protein-folding problem can be solved at the atomic detail level by an ab initio procedure, starting from random conformations, with no knowledge except the amino acid sequence. To our knowledge, the results reported here correspond to the largest protein ever folded from a random conformation by an initial-value formulation with a full atomic potential, without resort to knowledge-based information. For many years, methods have been developed to compute the 3D structures of polypeptides, based on empirical atomic-based potential energy functions and global optimization of such functions. Because of limitations in computer power, these methods have been confined to small molecules such as the pentapeptide enkephalin (1–15), the decapeptide gramicidin S (16–21), and linear fibrous proteins such as collagen-like repeating polytripeptides (22–24). Inclusion of explicit or implicit hydration in the potential function only exacerbated the global optimization problem. However, with the recent availability of cost-effective alternatives to large supercomputers, such as Beowulf class cluster computers (25), it is now possible to extend the application of such ab initio physics-based methods to larger molecules. In this article, we report the results of the global optimization of the all-atom force field ECEPP/3 (empirical conformational energy program for peptides) (26–29) plus two implicit hydration models [SRFOPT (Solvent Radii Fixed with atomic solvation parameters OPTimized; ref. 30) and OONS (Ooi, Oobatake, Némethy, and Scheraga solvation model; ref. 31)], using the electrostatically driven Monte Carlo (EDMC) method (32, 33) to explore the conformational space of the 10–55 fragment of the B-domain of the staphylococcal protein A molecule, efficiently. The structure of this fragment of the B-domain of the protein A molecule is known from x-ray (34) and NMR (35) investigations, and from minimalist and all-atom simulations (36–46). However, such initial-value-formulated simulations (except for ref. 46, which is a boundary-value formulation) were not started from a random conformation. Therefore, in this work, we attempted to provide an extensive exploration of the conformational space by starting from two different randomly chosen conformations, using a Beowulf class cluster.